Fiber morphological characteristics of bamboo Ferrocalamus strictus culms from different geographical distribution regions - Xiaofeng Zheng; Rui Xu; Honglan He; Jiamin Wang; Ziten Zhou; Hui Zhan; Yingqiong Wang; Jiayi Deng; Changming Wang (Journal of Wood Science)
Abstract The fiber index including fiber length, width, wall thickness and lumen diameter of Ferrocalamus strictus culms (1, 2, and ≥ 3 years) from Jinping, Mojiang and Lvchun counties of Yunnan Province was determined and the elemental content of the soil was also determined to analyze the fiber characteristics. The average relative fiber index measured for F. strictus culms were fiber length (1.30 mm), width (21.57 μm), slenderness ratio (60.79 μm), wall thickness (4.21 μm), lumen diameter (7.22 μm), and runkel ratio (1.22 μm), which belonged to the range of middle and long fibers. The fiber length increased with the culm age. The proportion of long fiber increased while short fibers decreased along with culm maturing. The fiber morphology did not show a specific trend with the culm height. Fiber length reached the maximum in the bottom portions of the culms. There is a correlation between fiber morphology and soil elements, the content of organic matter, total potassium, total sulfur, total aluminum, total zinc, total iron, total boron, alkali-hydrolyzed nitrogen and available silicon in the soil affects fiber morphology. The content of organic matter, total boron and alkali-hydrolyzed nitrogen in the soil from Mojiang County was largest. Comparatively, the culm fiber in Mojiang County had the best fiber index performance for utilization, since the greatest proportion of medium and long fibers and the optimal distribution of fiber length frequency was obtained from the culms in Mojiang County. This study can provide a theoretical basis for large-scale bamboo forest cultivation and the development and utilization of bamboo culm fiber.